2021
DOI: 10.1155/2021/5559021
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Model of Carbon Footprint of Fresh Products in Cold Chain from the Energy Conservation and Emission Reduction Perspective

Abstract: The carbon footprint of the cold chain logistics system refers to the greenhouse gas emissions directly or indirectly caused in each link of the cold chain logistics activities. Because cold chain logistics is the main carbon emitter in the field of logistics, research on how to reduce carbon emissions in the field of cold chain logistics plays an important role in energy conservation and emission reduction. Based on the in-depth analysis of the carbon footprint of cold chain logistics, this paper introduces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Li et al . (2022b) and Hu et al . (2021) adopted above approach, where the environment cost was obtained through the unit price and carbon emission determined based on emission factor.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Li et al . (2022b) and Hu et al . (2021) adopted above approach, where the environment cost was obtained through the unit price and carbon emission determined based on emission factor.…”
Section: Literature Reviewmentioning
confidence: 95%
“…By analyzing existing research, it is found that many scholars convert carbon emission into carbon emission cost when studying cold chain logistics vehicle routing problems (Li et al, 2019a). Li et al (2022b) and Hu et al (2021) adopted above approach, where the environment cost was obtained through the unit price and carbon emission determined based on emission factor. At present, this method for calculating carbon emission cost has become the research mainstream (Chen et al, 2019;.…”
Section: Cold Chain Logistics Vehicle Routing Problemmentioning
confidence: 99%
“…Liu et al [19] showe d that a joint distribution is less costly than a single distributi on in terms of carbon emissions and that the total cost is posit ively related to the cost of carbon emissions. Hu et al [20] fir st used the cycle evaluation method and the input-output met hod to calculate the range of carbon emissions during each st age of cold-chain logistics. To develop a mathematical model for carbon footprint optimization, Ning et al [21] developed a quantitative analysis of the carbon tax mechanism.…”
Section: B Carbon Emissionsmentioning
confidence: 99%
“…Equations ( 3) and ( 4) indicate that vehicle k must leave and return to the depot. Restriction (5) forces each vehicle k to leave the node. Equation ( 6) represents the capacity constraint.…”
Section: Objective Functionmentioning
confidence: 99%
“…Some contracts with retailers involve penalties for delays within the established delivery times. Additionally, energy is required to maintain adequate temperature during distribution, and traffic conditions are different throughout the day [5]. Therefore, the impact of delays on delivering perishable food is more critical than general goods [6].…”
Section: Introductionmentioning
confidence: 99%